Lessons Learned From a Faulty Transoral Endoscopic Thyroidectomy Vestibular Approach. Issue 5 (October 2018) - Zhang, Daqi; Wu, Che-Wei; Inversini, Davide; Kim, Hoon Yub; Anuwong, Angkoon; Bacuzzi, Alessandro; Dionigi, Gianlorenzo
Abstract : Background: Transoral endoscopic thyroidectomy via vestibular approach (TOETVA) is currently considered the most promisingly scarless approach to the thyroid and has gained more acceptance. Materials and Methods: We described a case of faulty TOETVA. Results: The faulty TOETVA resulted in pneumomediastinum, diffuse subcutaneous emphysema, prolonged surgery, and anesthesia. Conclusions: The important technical considerations during TOETVA, including the use of external retraction, the identification of the subplatysmal plane of dissection, CO2 insufflation settings, the learning curve, and patient selection, were described and discussed.